2020
DOI: 10.4236/ojs.2020.105051
|View full text |Cite
|
Sign up to set email alerts
|

Causality Analysis on Export and Economic Growth Nexus in Ghana

Abstract: The study examined the causal relationship between export and economic growth based on monthly data for the period 2010 to 2019. Composite Index Economic Activity (CIEA) was used as a proxy for real GDP (economic growth). Time series econometric techniques were employed to explore long-run and short run relationships as well as the causality between them. The results revealed the existence of long-run relationships; evidence of bi-directional causality and a rapid adjustment to equilibrium between real GDP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(24 reference statements)
2
6
0
Order By: Relevance
“…Moreover, the investigation has confirmed the presence of a bidirectional link between variables in Denmark. This insight supports a feedback approach and the studies by Mah (2007), Sunde (2017), Guntukula (2018), Mensah andOkyere (2020), andAdebavo (2020). It is assumed, that the implementation of strategies to promote economic growth and exports could contribute to the achievement of sustainable development.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Moreover, the investigation has confirmed the presence of a bidirectional link between variables in Denmark. This insight supports a feedback approach and the studies by Mah (2007), Sunde (2017), Guntukula (2018), Mensah andOkyere (2020), andAdebavo (2020). It is assumed, that the implementation of strategies to promote economic growth and exports could contribute to the achievement of sustainable development.…”
Section: Discussionsupporting
confidence: 73%
“…From the literature review mentioned above, the inter-linkage between exports and economic development has been and still are a subject of intensive debate amongst researchers and policymakers, with inconclusive outcomes being reached along the way. The findings of investigations have varied across the countries involved (Trošt & Bojnec, 2015;Ee, 2016;Dinc & Gokmen, 2019;Sultanuzzaman et al, 2019;Fannoun & Hassouneh, 2019;Mensah & Okyere, 2020). This research has shown that evidence exists in regard to a correlation between exports and economic development.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The interrelationship between export and economic growth has been a subject of debate among the scientists for a long time (Smith, 1776;Feder, 1982;Fryges, 2009;Mishra, 2011;Wagner, 2012;Tekin, 2012;Abbas, 2012;Dritsaki, 2013;Saaed et al, 2015;Shafiullah et al, 2017;Guntukula, 2018;Sultanuzzaman et al, 2019;Mensah & Okyere, 2020;Adebayo, 2020). Scientific studies on the export-economic growth nexus provide controversial results.…”
Section: Introductionmentioning
confidence: 99%